Effect of different diets of full fat soybean (lake) on the meat composition of broilers - DS Rasane; SS Kamble (Journal of Livestock Biodiversity, 2025)
In the three feeding trials of broilers the meat composition at 6 weeks and 8 weeks age was studied. The meat composition at 6 weeks age indicated that the water content in Trial-I, II and III irrespective feed treatment ranged from 73.23 to 74.70 per cent. The corresponding values at 8 weeks age ranged from 71.70 to 72.75 per cent. There was no significant difference in all the treatments as well as all the trials. However, water content in the meat of birds at advanced age (8 weeks) was comparatively less than 6 weeks age. The protein content of meat at 6 and 8 weeks age ranged from 18.06 to 18.25 per cent. The protein percentage of meat was neigher affected by treatment diets nor by different trials. The fat content in meat at 6 weeks age ranged from 6.03 to 7.33 per cent in all treatments and all the three trials. At 8 weeks age fat content in meat was ranged from 7.83 to 8.90 per cent. The fat content of meat was higher in T3 followed by T2 , T1 and T0 in all the trials. The fat content of meat at 8 weeks was signi icantly higher than 6 weeks meat in all the treatment diets of all the trials. The ash content in the meat at 6 weeks age amongst the three trials did not show much differences and remained almost similar. Similar trend was observed 8 weeks age however the results indicated that ash content in the meat higher at increasing age. Amongst the different treatment diets ish meal containing diet (T0 ) showed higher ash percentage. The ash content in the meat was in decreasing order with increase in FFSB level in the diet. In T containing diet meat ash content was significantly lower than T0 , T1 and T2 .